EXPLORING TEACHERS TECHNIQUE IN TEACHING ENGLISH OF BILINGUAL CLASS AT SMP NEGERI 1 KOTA TERNATE - Ratih Virginia A. Wally; Naniek Jusnita; Fitria Wulan Sari (Jurnal Bilingual, 2023)
This study aims to determine the teacher's technique in teaching English in bilingual class written by students of the English language education study program at Khairun University. This study uses a qualitative descriptive method in data collection and analysis. The instruments used were observation and interviews. The results of this study involved 1 subject, namely an English teacher, especially those who teach in bilingual class. From the results of this study, there are several teaching techniques that are used and some that are not used by the teacher to teach in bilingual class. Of the 8 techniques proposed by Amidinah (2015), there are only 3 techniques used during the learning process in the classroom. Those are panel discussion techniques, assignment techniques, and also questionanswer techniques. While the techniques that are not meant are lecture methods, discovery and simulation techniques, Inquiry techniques, travel technique and also experimental techniques. So the reason behind those techniques that do not occur in this teaching process is because they are adapted to the conditions and learning materials taught by the teacher in the classroom. where for travel techniques require students to study outside the classroom, experimental techniques are present if the material taught by the teacher is related to observing an object, lecture techniques only focus more on the teacher, while for discovery and simulation techniques only focus on understanding concepts, meanings and relationships, through an intuitive process to draw a conclusion from the learning material.